A Low‐Cost Method to Evaluate Absorber Reflectivity Using an Antenna with a Small Radiating Aperture and Frequency‐Domain Instrument. Issue 6 (4th December 2013) - Oh, Soon‐Soo; Lee, Young Hwan
Abstract : We propose a way to measure the absorber reflectivity at a low cost. Only one simple antenna with a small radiating aperture and a frequency‐domain instrument are utilized. The previously used equation for calculating the reflectivity of an absorber is inaccurate, and, therefore, a new equation is derived based on multiple reflection analysis and three test models. Notably, the reflection coefficient of the antenna is included in the derived equation. The accuracy of the proposed method is proven through simulation and measurements. It can be easily applied to a product examination by absorber manufacturers and customers owing to its advantages of simplicity, cost effectiveness, and non‐cutting examination.